Experimental Study on the Influence Factors of Flow Velocity Structure and Turbulent Characteristics in Open Channel with Biomimetic Grass - Changjing Fu; Jinguo Wang; Tianlong Zhao; Yi Lv (Advances in Civil Engineering)
The problem of suspension treatment of subsea oil-gas pipelines has been highly concerned by engineering construction units and researchers. The current research indicates that the bionic sea grass can effectively reduce the flow rate, promote sediment deposition, and control the development of the pipeline suspension area. The velocity distribution of open channel flow with bionic grass is very complex. The height and laying space of bionic grass will affect the flow velocity distribution. At present, the flow velocity in open channels with bionic grass is mainly studied by measuring the velocity variation at the front, middle, and back of bionic grass. Few effective measurements are made for the full velocity field. The velocity field distribution of bionic aquatic grass along the vertical plane is measured by using standard particle image velocimetry (PIV). The effects of height and laying space of bionic grass on probability density distribution, spatial correlation of pulsating velocity, turbulence intensity, Reynolds stress and turbulent kinetic energy in the open channel after the protection section of bionic grass are further analyzed.